Kajian Proses Sterilisasi Media Jamur Tiram Putih Terhadap Mutu Bibit Yang Dihasilkan - Desna, Desna; Puspita, R. D.; Darmasetiawan, H.; Irzaman, Irzaman; Siswadi, Siswadi (BERKALA FISIKA, 2010)
Sterilization media were done in drum. Fuels LPG.is used for the fuel Efficiencies of the fuel gained in the media sterilization oyster mushrooms for 6 hours is 40.74%, meanwhile efficiencies of the fuel for 8 and 10 hours is 59.57% and 53.14%. The physical and economical research of the white oyster mushrooms sterilization process for 8 hours produces the highest efficiency. Â Keywords: Medium, oyster mushrooms, LPG, sterilizationÂ